The Blackwell companion to social theory - Blau,Judith R. (Blackwell, 1996)
The Blackwell Companion to Social Theory brings together leading scholars from around the world to provide the first truly international overview of the major developments in twentieth-century Western social thought. Edited and introduced by Bryan S. Turner, this volume aims not only to chart the main thinkers, schools, and movements within contemporary social theory, but also to identify points of convergence and possibly synthesis, particularly between North American and European traditions.